Quality of Nurse Work Life in Pangandaran Health Center - Irman Somantri; Kurniawan Yudianto (Jurnal Keperawatan Padjadjaran, 2018)
Quality service is the main goal of the health care system, where the purpose of service quality is to ensure that the services or products of nursing services are produced according to the patient’s standards / desires. The purpose of this study was to find out the quality of work life of nurses in the Puskesmas.This study uses correlative design that connects the characteristics with the quality of the work life of nurses. The research sample was 48 nurses in Puskesmas who were taken by total sampling. Comparative test was carried out using Mann Whitney, Kruskall Wallis and Spearman tests adjusted for the type of dataThe results are displayed in the form of numerical data tables consisting of middle values, deviations and probability values. The total quality of work life of nurses in Pangandaran Health Center was 145.83 where the value obtained was below the average standard value of 150. Likewise for the aspect of work environment, relations with managers, work conditions and job perceptions which had a mean below the standard mean while the support service aspect has an average of 19.31 while the average standard is 18. Based on the comparative analysis, gender and age have no relationship with the quality of work life (p Value> 0.005), while the level of education, the number of teams and salaries have a relationship with quality working life of nurses in Pangandaran Health Center (p Value <0.001). This means that nurses have not felt well in their work, except in the aspect of support service in this aspect nurses have felt satisfied and prosperous in getting support from other teams / officers. Likewise, the level of education, the number of teams and salaries have an influence on the quality of the worker’s life.